Article Withdrawal by ASERS Publishing - Fraudulent double submission and legal limitations - The Main Directions of Improving the Environmental and Economic Efficiency of Regional Production - SYCHEVA, Irina; VORONKOVA, Olga; VOROZHEYKINA, Tatiana; YUSUPOVA, Gulnara; SEMENOVA, Albina; ILYIN, Aleksey (Journal of Environmental Management and Tourism, 2019)
The paper provides theoretical grounding and the directions for improving the economic efficiency of the regional feedstuff production. The study develops a conceptual model of distributing management functions of feedstuff production between the regional authorities of state sectoral and economic management and the district level. The authors suggest the methodology for calculating potential capacity of intraregional feedstuff market, considering the demands of all categories of agricultural manufacturers. The study examines possibilities for implementing the strategy of diversified growth and development of the intraregional feedstuff market, including the terms of interaction between the large and micro-business inside the industry and cooperation of micro-business feedstuff manufacturers with agricultural production. The authors have developed the methodology for assessing the efficiency of feedstuff production, based on the aggregate estimation of the management organization, conditions for the development of feedstuff production and changes in the feedstuff production and livestock breeding industry.